Origin of impulsive plasma outflows due to magnetoacoustic shocks - Rao Y.K.; Srivastava A.K.; Doyle J.G.; Dwivedi B.N. (My University, 2025)
We study an impulsive plasma outflow in the quiet-Sun using multiwavelength observations from the Atmospheric Imaging Assembly (AIA) onboard the Solar Dynamics Observatory (SDO) on 2011 March 30. The outflow rises to the upper solar atmosphere with a high terminal speed of 1250 km s-1. Emissions from multiple SDO/AIA channels (log T (K) = 4.7 to log T (K) = 7.0), peak at the same time indicating its highly impulsive origin. We obtain the line-of-sight differential emission measure maps and find that the outflow is made up of multitemperature plasma. Investigation of SDO/HMI magnetic field data at its footpoint shows that the emerging flux of negative polarity is oscillating at the period of 442 s. The oscillations are also observed in the intensity of 1600 Å almost co-temporally at the base of the outflow with the almost same period (≈416 s). The ~7.0 min periodicity in the magnetic flux and 1600 Å flux is present both prior to and during the onset, and even after the outflows for the duration of ≈1 h. This indicates that the magnetoacoustic waves are generated and present at the base of the outflow and interact with the localized small-scale current sheet and associated X-point. Magnetoacoustic waves encounter with the discontinuity at the X-point that may further develop into the fast magnetic shocks leading to the formation of the observed shock cusp and triggering of the impulsive plasma outflows. © 2017 The Authors. Published by Oxford University Press on behalf of the Royal Astronomical Society.